PENERAPAN METODE FAST FIRING PROCESS PADA PEMBUATAN KERAMIK UKIR JENIS STONEWARE - M. Dachyar Effendi (Jurnal Energi dan Lingkungan (Enerlink), 2009)
To reduce energy consumption in ceramic process, Investigation of fast firingmethode to produce relief product has been carried out. Best Ceramiccomposition applied to produce rellief without defect when burned in normal firingtraject. The composition consists of Kalimantan clay :52,5 %, Penujak clay 10%,Felspar RRC 16%, Talk 2,00 – 5,00%, limestone 2,5% - 6,50% and Ballclay13,00 – 13,50% and agree with stoneware qualification. In this research, Desiredtemperature reached at 7 hour, decreased 2 hour compare to normal firingtraject. Crack occured on some rellief products indicated that the product withdiffer thickenness significantly along ceramic body can not be applied into fastfiring process.Kata kunci: keramik ukir, stoneware